Entrepreneurship Training and Socialization In The Use of Waste Based On Community Empowerment In Kumantanvillage Bangkinang District, Kampar Regency, Pekanbaru, Riau - Mariaty Ibrahim; Mashur Fadli; Suryalena Suryalena; Endang Sutrisna (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This training and socializing aims to impart knowledge to people with creativity, small businesses/small industries, and those who have yet to start a business. It is hoped that existing human resources would be able to carry it out with the help of training and entrepreneurial socialization. When starting a business, increased knowledge and talents are expected to boost the organization's overall performance. Entrepreneurship Training and Socialization are implemented through lecture, discussion, and practice processes at the service location. To attain development goals in all disciplines, entrepreneurship training and community socialization activities must be strengthened, demanding the attention of all interested parties. The government's and community leaders' motivation must be maintained and increased for the community to get more information and skills linked to business growth and raise community and regional revenue, particularly in Kuantan Village, Bangkinang District, Kampar Regency.